Lithobius (Monotarsobius) tetrasulcus sp. n., a new species of centipede from China (Lithobiomorpha, Lithobiidae) - Sujian Pei; Haipeng Liu; Kuijing Liang; Huiqin Ma; Yanmin Lu (Biodiversity Data Journal, 2021)
The myriapod fauna of China is still poorly known and very little attention has been paid to the study of Lithobiomorpha, with only 100 species and subspecies known from the country. Altogether, 11 species of subgenus Monotarsobius have been recorded from China, but only two of them have been reported from Hebei Province. Herein, a new species recently discovered in the Hebei Province, China, is described and illustrated.A new lithobiids species Lithobius (Monotarsobius) tetrasulcus sp. n. is described and illustrated from Hengshui Lake National Nature Reserve, Hebei Province, China. The new species is compared with Lithobius (Monotarsobius) crassipes Koch, 1862 from Taiwan, China. It can be easily distinguished from congeners by having a longitudinal groove on the dorsal side of the femur and tibia of the male legs 14 and 15, only having a posterior spine on the dorsal side of femur of legs 12–15, lacking robust spines lying dorsally on the external margin on the second article of the female gonopods and the third article of the female gonopods having a bidentate apical claw.